Sequencing Halal Tourism Development in Merangin Jambi Geopark: An ASOCA Assessment - Arief Musvidi; Zulfanetti Zulfanetti; Lucky Enggrani Fitri (Education and Sociedad Journal, 2025)
Halal tourism has become an instrument of destination competition across Muslim-majority regions, yet the question of how a newly designated geological heritage site should order its development priorities has received little attention. This study examines the potential, readiness, obstacles and strategic priorities for halal tourism development in Merangin Jambi UNESCO Global Geopark, Jambi Province, Indonesia. A qualitative field design was applied with ten purposively selected informants drawn from the Regional Tourism Office, the Office of Cooperatives, Small and Medium Enterprises, Trade and Industry, the village government of Air Batu, and local tourism operators. Data were collected through semi-structured interviews, a structured questionnaire, field observation and document review, then analysed with the ASOCA framework, which combines ability, strength, opportunity, culture and agility, followed by a Litmus test that scored fifteen strategic issues on a range from ten to thirty. The geopark holds substantial natural and geological capital together with a religiously observant host society, while readiness remains uneven in certified facilities, workforce capability and inter-agency coordination. Obstacles are primarily institutional, including burdensome certification, weak regulatory synchronisation, passive community participation, and the absence of a permanent stakeholder forum. Litmus scoring placed prayer and ablution facilities highest at twenty-eight, followed by halal lodging and dining at twenty-seven, workforce training with certification and community involvement at twenty-six, while culture-oriented strategies clustered between eighteen and twenty-two. Opportunity-facing strategies averaged 24.56 against 21.33 for culture-facing strategies. The study concludes that halal tourism readiness follows a sequenced logic where service foundations precede cultural differentiation, and proposes a three-phase development pathway for regency policy.